PENGARUH PERTUMBUHAN EKONOMI DAN UPAH MINIMUM TERHADAP TINGKAT KEMISKINAN DI KABUPATEN DAN KOTA PROVINSI BANTEN - Siti Mudawanah (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2022)
This research was conducted to test whether the variables of economic growth and minimum wages have an effect on the poverty rate in the districts and cities of Banten province.The research method used is a quantitative analysis approach, and in testing research data using the help of an analysis tool, namely Eviews. The population for this study is all data on economic growth, minimum wages and poverty rates in the districts and cities of Banten province for the 2011-2019 period. The sample technique uses the saturation technique, namely using all regencies and cities of Banten Province in 8 regions.The results and conclusions show that partially economic growth and minimum wages have no effect on poverty levels. While simultaneously economic growth and minimum wages affect the level of poverty